2001
DOI: 10.1518/001872001775870421
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Air Traffic Controller in Future Air Traffic Management: An Empirical Study of Active Control versus Passive Monitoring

Abstract: Proposals for air traffic management such as Free Flight call for a transfer of responsibility for separation between aircraft from air traffic controllers (ATCos) to pilots. Under many proposals, the role of the ATCo will change from one of active control to passive monitoring. The present study directly compared these types of control with respect to ATCo mental workload, conflict detection, and memory. Eighteen ATCos participated in an air traffic control simulation of Free Flight procedures under moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 17 publications
5
90
0
1
Order By: Relevance
“…This failure has been termed complacency (Hoc, 2001;Parasuraman, Molloy, & Singh, 1993;Smith, McCoy, & Layton, 1997) and has been mainly studied in supervision tasks that imply automation or computers (for example, car driving: Hoc et al, 2006;airline pilots: Layton, Smith, & McCoy, 1994; air traffic control: Metzger & Parasuraman, 2001). However, other tasks that are only partially automated, such as those found in manufacturing scheduling, are also affected by this problem.…”
Section: Introductionmentioning
confidence: 99%
“…This failure has been termed complacency (Hoc, 2001;Parasuraman, Molloy, & Singh, 1993;Smith, McCoy, & Layton, 1997) and has been mainly studied in supervision tasks that imply automation or computers (for example, car driving: Hoc et al, 2006;airline pilots: Layton, Smith, & McCoy, 1994; air traffic control: Metzger & Parasuraman, 2001). However, other tasks that are only partially automated, such as those found in manufacturing scheduling, are also affected by this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggested the advantage of active control over passive monitoring in air traffic management (e.g., Metzger & Parasuraman, 2001). Our findings can be applied to the design and evaluation of interfaces that keep the controller in the loop.…”
Section: Discussionmentioning
confidence: 99%
“…Third, automatic control can induce the operator to disengage and direct attention to other activities, further compromising the feedback from the system. The tendency to rely complacently on automation, particularly during multitask situations, may reflect this tendency to disengage from the monitoring task (Parasuraman et al, 1993(Parasuraman et al, , 1994Metzger and Parasuraman, 2001). Finally, the operator's mental model may be inadequate to guide expectations, situation awareness, and control.…”
Section: Out-of-the-loop Unfamiliaritymentioning
confidence: 99%